Nanostructured donor-acceptor self assembly with improved photoconductivity - Saibal, B.; Ashar, A. Z.; Devi, R. Nandini; Narayan, K. S.; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Nanostructured supramolecular donor-acceptor assemblies were formed when an unsymmetrical N-substituted pyridine functionalized perylenebisimide (UPBI-Py) was complexed with oligo(p-phenylenevinylene) (OPVM-OH) complementarily functionalized with hydroxyl unit and polymerizable methacrylamide unit at the two termini. The resulting supramolecular complex [UPBI-Py (OPVM-OH)](1.0) upon polymerization by irradiation in the presence of photoinitiator formed well-defined supramolecular polymeric nanostructures. Self-assembly studies using fluorescence emission from thin film samples showed that subtle structural changes occurred on the OPV donor moiety following polymerization. The 1:1 supramolecular complex showed red-shifted aggregate emission from both OPV (similar to 500 nm) and PBI (similar to 640 nm) units, whereas the OPV aggregate emission was replaced by intense monomeric emission (similar to 430 nrn) upon polymerizing the methacrylamide units on the OPVM-OH. The bulk structure was studied using wide-angle X-ray diffraction (WXRD). Complex formation resulted in distinct changes in the cell parameters of OPVM-OH. In contrast, a physical mixture of 1 mol each of OPVM-OH and UPBI-Py prepared by mixing the powdered solid samples together showed only a combination of reflections from both parent molecules. Thin film morphology of the 1:1 molecular complex as well as the supramolecular polymer complex showed uniform lamellar structures in the domain range <10 rim. The donor-acceptor supramolecular complex [UPBI-Py (OPVM-OH)](1.0) exhibited space charge limited current (SCLC) with a bulk mobility estimate of an order of magnitude higher accompanied by a higher photoconductivity yield compared to the pristine UPBI-Py. This is a very versatile method to obtain spatially defined organization of n and p-type semiconductor materials based on suitably functionalized donor and acceptor molecules resulting in improved photocurrent response using self-assembly.
Keywords: donor-acceptor; hydrogen bonding; oligo(p-phenylenevinylene); Perylenebisimide; photoconductivity; supramolecular polymeric nanostructures